2018
DOI: 10.2147/ijn.s173279
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal codelivery of an SN38 prodrug and a survivin siRNA for tumor therapy

Abstract: PurposeA liposome-based siRNA–drug combination was evaluated as a potential therapeutic strategy to improve the curative effect.MethodsA topoisomerase inhibitor SN38 prodrug was combined with a survivin siRNA through codelivery using transferrin (Tf)-L-SN38/P/siRNA. In this combination, SN38 was conjugated to the cell penetrating peptide TAT through a polyethylene glycol (PEG) linker to synthesize TAT-PEG-SN38. The amphiphilic TAT-PEG-SN38 was used as an ingredient of liposomes to improve the cellular uptake. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…SN38 is an active metabolite of the first-line drug irinotecan, with strong anti-tumor effects. However, due to the limited water solubility, unstable properties, drug resistance, and adverse reactions of SN38, its widespread clinical application is limited [ 22 ]. Nano-delivery system can increase the solubility of SN38, reduce its toxic side effects on normal tissues, and improve anti-tumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…SN38 is an active metabolite of the first-line drug irinotecan, with strong anti-tumor effects. However, due to the limited water solubility, unstable properties, drug resistance, and adverse reactions of SN38, its widespread clinical application is limited [ 22 ]. Nano-delivery system can increase the solubility of SN38, reduce its toxic side effects on normal tissues, and improve anti-tumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“… ( Alphs et al, 2016 ; Corena-McLeod, 2015 ) Natural Product SN 38 Anti-proliferative and anti-tumor roles by activating MAPK pathways and boosting IL-8 expression. ( Bi et al, 2018 ; Zhang et al, 2017 ) Bicuculline The antagonist of receptors of inhibitory neurotransmitter GABA and enhances calcium secretion. ( Johnston, 2013 ; Mestdagh and Wülfert, 1999 ) Columbianadin Anti-cancerous and anti-inflammatory effects by inducing necroptosis and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 112 siRNA combined with chemotherapeutic drugs will become a new strategy for efficient tumor treatment, with good prospects for clinical translation. Bi et al 113 prepared transferrin (Tf) liposomes co-loaded with TAT-PEG-SN38 and survivin siRNA (Tf-L-SN38/P/siRNA). This liposome was able to increase endocytosis and consequently cytotoxicity in HeLa cells, and the results of in vitro cellular experiments revealed that Tf-L-SN38/P/siRNA (IC 50 =175 nM) exhibited stronger cytotoxicity compared with Tf-L-SN38 (IC 50 =2.03 μM) and SN38 (IC 50 =2.55 μM) in HeLa cells.…”
Section: Co-delivery Drug Delivery Systemmentioning
confidence: 99%